Зимняя сказка: [для старшего дошкольного и младшего школьного возраста] / художники Ирина Егорова, Михаил Пыльцын, Игорь Шляхов - Егорова Ирина (Проф-Пресс, 2017)
Экземпляры: ф30 (20200129) / Инвентарный номер: 58981 / Цена: 200.00 / Сис.шифр: Д / Авт.знак: З-62 / ГРНТИ: 17.82.93 / ББК: 84(0)